The development of a sensor system for monitoring the displacement of horizontal laterals in Radial Drilling Technology - Ziaja, Jan; Movčan, Vasil' (Wydawnictwa AGH, 2017)
Radial drilling technology was developed by Rad Tech international inc., an American company set up by Henk Jelsma, its permanent head and the technology patent holder. First introduced in the Americas, radial drilling technology acquired wide recognition in the USA and Colombia and later found applications in Canada, Bolivia, Argentina, Chile and the Middle East. In general, this technology is aimed at extending and improving drainage areas in productive formations. Other applications of radial drilling include the creation of specifically directed injection channels and exploration activities. Performance testing of these short radius laterals has not been adequately studied and significant questions remain about how well these technologies can deliver on their promises. The main objective of the paper is to sum up previous experience in developing a system for monitoring the displacement of horizontal laterals and wells, and examining a prospective new technology which can increase the efficiency of radial drilling.
AGH Drilling, Oil, Gas
Bibliogr. s. [881].
Keywords: hydraulic system; deflector shoe; sensor development; optical fiber sensor